RETRACTED: Local hemostatic biomaterial based on native collagen - Radjabov O.I.; Otajonov A.Y.; Baratov K.R.; Azimova L.B. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001